Keteladanan Mahasiswa PLP dalam Meningkatkan Kepedulian Siswa terhadap Kebersihan Sekolah di SMAN 1 Lasusua - MGB, A. Ilmadana; Sandi; Akram; Suhra Dewi; Jusvyna Nurul Ilmah; Nabila; Takwa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of students’ awareness toward school environmental cleanliness remains a challenge in character building at SMAN 1 Lasusua. Although students generally understand the importance of cleanliness cognitively, they often fail to implement it in their daily behavior. Therefore, this Community Service Program (PKM) aims to improve students’ awareness through the role modeling of students involved in the Field Experience Program (PLP). The method used is Participatory Action Research (PAR), which involves PLP students, mentor teachers, and students collaboratively through the stages of planning, action, observation, and reflection. Role modeling is implemented through the habituation of positive behaviors such as discipline, responsibility, empathy, and environmental awareness. The results show significant behavioral changes, including increased concern for school cleanliness, improved empathy among students, and stronger responsibility and active participation in learning activities. In addition, a more conducive classroom environment and sustainable positive habits were established. Thus, the role modeling of PLP students is proven to be an effective strategy in enhancing students’ awareness, particularly when implemented consistently and supported by a conducive school environment.